Process and Quality of Canned Baby Corn Juice - Kulvadee Trongpanich; Rasamee Supasri; Srimaung Maleehual (Agriculture and Natural Resources, 1990)
The study on the process of canned baby corn juice and drink was carried out. Pulper and the screw and hydraulic press were used in the juice extraction processes. Results of organoleptic test, indicated that Thai teaters prefered diluted drink more than juice or more concentrated ones. The color, taste, odor, turbidity and nutritive values of the juice were more intense than those of the drink. Such characters of the products from the pulper were more intense than those of the products from the screw and hydraulic press. The minimum process times of canned baby corn juice and drink at 115.6oC were found to be 25 and 20 mins. respectively